Pengaruh Flexible Work Arrangements dan Workplace Loneliness terhadap Workplace Loneliness - Mukhlish, Dawam; Kistyanto, Anang (Universitas Negeri Surabaya, 2024)
This study aims to test and analyze the effect of flexible work Arrangements and workplace loneliness on worker Well-Being. This study uses a quantitative approach involving 44 employees of PT XYZ. The sampling technique uses probability sampling with a saturated sample type, as many as 44 respondents with online google form questionnaire data collection. The data analysis technique in this study uses Structural Equation Modeling - Partial Least Square (SEM PLS) using SmartPLS 3.2.9 software. The results of this study indicate that wlexible work arrangements have a significant positive effect on worker well-Being, and workplace woneliness has a significant positive effect on worker well-Being.